Faculty Perceptions of Government and Management - Cummings, William; Fisher, Donald; Locke, William (International Higher Education, 2010)
A model of higher education decision-making was prevalent with shared governance. To assess faculty perceptions of the current state of higher educational governance and management, the Changing Academic Profession (CAP) project went to the field in 2007 in 18 countries. In most of the countries, faculty were more likely to perceive they have authority individually or through academic committees and boards. There is a decline in the institutional loyalty of academics from a similar survey conducted in 1992.